Educational activity on stress in the academic environment: experience report (Research, Society and Development, 2023)
Report the experience of identifying stressors in the academic environment. This is a descriptive study, of the experience report type, based on the Problematization Methodology, according to the Arch of Maguerez, carried out by students of the Nursing course at the University of the State of Pará (UEPA) for Integrated Health Actions (AIS). As a result, based on the students' reports, it was possible to identify the main stressors, namely: adaptation to the academic environment, excessive academic activities, impaired social life, and the relationship with other psychological problems, such as anxiety. In view of this, the lived experience was of great relevance, since this study allowed us a greater understanding of the theme, with regard to the panorama of the occurrence of stress among academics and the possibilities of coping. Also, the meaning of the Problematization Methodology is highlighted, since it brings the student closer to reality, which enables the improvement of faster and more effective resolution skills.